The Fund's Mandate-Future Financing Role. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2010)
The following is the provisional agenda for the Twenty-First Meeting of the International Monetary and Financial Committee, which is to be convened at the Fund's Headquarters in Washington, D.C. on Saturday, April 24, 2010. A joint working dinner of IMFC members and G-20 ministers will be held on Friday, April 23 at 7:30 pagesm. in HQ1-Meeting Halls A and B. The IMFC meeting will be followed by the press conference of the IMFC Chairman and the Managing Director at 2:30 pagesm.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet